2014
DOI: 10.1002/0471142956.cy0946s68
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of Paucicellular Samples

Abstract: Immunophenotyping of paucicellular samples may represent a diagnostic challenge in the flow cytometry (FC) laboratory routine, as the scarcity of cells limits the number of tests that can be performed. Specimens such as fine needle aspirates (FNA), human body fluids (BF), cerebrospinal fluid (CSF), or ocular fluid (OF) sent for FC investigations in the case of suspicion of lymphoma, or for lymphoma monitoring, may contain very low numbers of cells. In these cases, it is mandatory to obtain the largest amount p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…The overall rationale of the analysis and of the gating strategy applied has been previously published [11]. Examples of the STA protocol with the different cytometers utilized in this study are showed in figures 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall rationale of the analysis and of the gating strategy applied has been previously published [11]. Examples of the STA protocol with the different cytometers utilized in this study are showed in figures 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the set-up of a single tube, based on patient information and clinical suspicion, is frequent in FC laboratory practice. In this study, we report our experience with an FC assay that was developed in order to gather the greatest amount of information from hypocellular samples sent for lymphoma suspicion or monitoring [11]. The method used different MoAbs cocktailed in one tube to detect and identify lymphocytes, as well as a logical gating strategy to gate out dead cells and get rid of debris and clumped cells (doublets).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of fluids and aspirates may entail a very limited number of cells and only a single tube to run FC investigations. In these cases, tailored antibody panels should be designed on the basis of clinical features, patient history and specimen source [13]. …”
Section: Fc Specimen Sourcementioning
confidence: 99%